2017
DOI: 10.3389/fmolb.2017.00088
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Human D-Amino Acid Oxidase

Abstract: D-amino acid oxidase catalyzes the oxidative deamination of D-amino acids. In the brain, the NMDA receptor coagonist D-serine has been proposed as its physiological substrate. In order to shed light on the mechanisms regulating D-serine concentration at the cellular level, we biochemically characterized human DAAO (hDAAO) in greater depth. In addition to clarify the physical-chemical properties of the enzyme, we demonstrated that divalent ions and nucleotides do not affect flavoenzyme function. Moreover, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 53 publications
1
64
0
Order By: Relevance
“…Moreover, we anticipate that the proportion of D-Pro may become a new brain health index in connection with cognitive function. Furthermore, with regard to chiral metabolism, D-Pro is decomposed and discharged by D-amino acid oxidase (DAO, EC 1.4.3.3) 34 . DAO catalyses the stereospecific oxidative deamination of the D-form of neutral amino acids, generating neurotoxic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we anticipate that the proportion of D-Pro may become a new brain health index in connection with cognitive function. Furthermore, with regard to chiral metabolism, D-Pro is decomposed and discharged by D-amino acid oxidase (DAO, EC 1.4.3.3) 34 . DAO catalyses the stereospecific oxidative deamination of the D-form of neutral amino acids, generating neurotoxic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Free D-serine is primarily localized in the mammalian forebrain, along with the highest concentrations of NMDA receptor [ 104 , 105 , 106 ]. D-Serine is created by serine racemase by converting L-serine into D-serine, which it is metabolized by DAAO [ 42 , 43 , 83 ]. D-Serine has a beneficial role in the brain and recent studies have broadened this story by showing how D-serine levels are regulated to protect the brain from damage or become dysregulated, causing disease [ 107 , 108 , 109 ].…”
Section: Nmda Receptor Agonists or Co-agonistsmentioning
confidence: 99%
“…There has been recent work to show that D-cysteine promotes the dendritic development of cerebellar Purkinje cells by a H2S mechanism [ 147 ]. Furthermore, it has been recently shown that human DAAO shows the greatest affinity for D-cysteine in spite of D-serine being expressed in the brain at much higher levels [ 42 ]. There has also been some dissenting work in this field, which hints at a more complicated story.…”
Section: Inactive D-amino Acids With Interesting Derivatives or Otmentioning
confidence: 99%
See 2 more Smart Citations